2018
DOI: 10.1016/j.ultramic.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

MS–STEM–FEM: A parallelized multi-slice fluctuation TEM simulation tool

Abstract: Atomic configurations of glassy or amorphous materials containing medium-range order (MRO) may be identified by comparing fluctuation transmission electron microscopy (FTEM) measurements to FTEM simulations obtained using model configurations. Candidate model sizes have traditionally been much thinner than the samples measured experimentally, and publicly available FTEM simulation software has until now omitted microscope parameters, dynamical scattering, and the phase of the diffracted electron wave. We intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…While a previous study 22 shows similar variance of MROR and MROC structures, our results show that the variance of MROR is slightly larger than that of MROC. This may originate from the number of orientations for the FEM simulation 42 ; the previous study 22 used 50 orientations and we used more than 200 orientations and confirmed the convergence with respect to the number of orientations. III.…”
Section: Iib Fluctuation Electron Microscopysupporting
confidence: 69%
“…While a previous study 22 shows similar variance of MROR and MROC structures, our results show that the variance of MROR is slightly larger than that of MROC. This may originate from the number of orientations for the FEM simulation 42 ; the previous study 22 used 50 orientations and we used more than 200 orientations and confirmed the convergence with respect to the number of orientations. III.…”
Section: Iib Fluctuation Electron Microscopysupporting
confidence: 69%